JMJD8 Regulates Angiogenic Sprouting and Cellular Metabolism by Interacting With Pyruvate Kinase M2 in Endothelial Cells. Issue 7 (July 2016) - Boeckel, Jes-Niels; Derlet, Anja; Glaser, Simone F.; Luczak, Annika; Lucas, Tina; Heumüller, Andreas W.; Krüger, Marcus; Zehendner, Christoph M.; Kaluza, David; Doddaballapur, Anuradha; Ohtani, Kisho; Treguer, Karine; et al.
Abstract : Objective—: Jumonji C (JmjC) domain–containing proteins modify histone and nonhistone proteins thereby controlling cellular functions. However, the role of JmjC proteins in angiogenesis is largely unknown. Here, we characterize the expression of JmjC domain–containing proteins after inducing endothelial differentiation of murine embryonic stem cells and study the function of JmjC domain–only proteins in endothelial cell (EC) functions. Approach and Results—: We identified a large number of JmjC domain–containing proteins regulated by endothelial differentiation of murine embryonic stem cells. Among the family of JmjC domain–only proteins, Jmjd8 was significantly upregulated on endothelial differentiation. Knockdown of Jmjd8 in ECs significantly decreased in vitro network formation and sprouting in the spheroid assay. JMJD8 is exclusively detectable in the cytoplasm, excluding a function as a histone-modifying enzyme. Mass spectrometry analysis revealed JMJD8-interacting proteins with known functions in cellular metabolism like pyruvate kinase M2. Accordingly, knockdown of pyruvate kinase M2 in human umbilical vein ECs decreased endothelial sprouting in the spheroid assay. Knockdown of JMJD8 caused a reduction of EC metabolism as measured by Seahorse Bioscience extracellular flux analysis. Conversely, overexpression of JMJD8 enhanced cellular oxygen consumption rate of ECs, reflecting an increased mitochondrial respiration. Conclusions—: Jmjd8 is upregulated during endothelial differentiation and regulates endothelial sprouting and metabolism by interacting with pyruvate kinase M2. Abstract : Supplemental Digital Content is available in the text.